1965
DOI: 10.1192/bjp.111.470.51
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Morbidity of West Indian Immigrants in an Urban Group Practice

Abstract: Since 1948 a number of papers published in Great Britain have demonstrated the feasibility of studying the incidence and prevalence of both major and minor psychiatric disorders in general practice (3, 4, 7, 8, 10, 11, 14, 16, 17, 18). Few, however, have focused on the health of West Indian immigrants in Great Britain, some 125,000 of whom have entered the country since that time (2, 12, 13, 20). This paper reports on the results of a six-month psychiatric morbidity survey of a group general practice in Brixto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1
2

Year Published

1967
1967
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 8 publications
0
22
1
2
Order By: Relevance
“…This agrees with Pinsent's studies among West Indians in Birmingham (17), and disagrees with those of Kiev (11) in London and Burke (3) in the West Indies. As expected, all groups of male schizophrenics were less likely to be married than female schizophrenics.…”
contrasting
confidence: 42%
See 1 more Smart Citation
“…This agrees with Pinsent's studies among West Indians in Birmingham (17), and disagrees with those of Kiev (11) in London and Burke (3) in the West Indies. As expected, all groups of male schizophrenics were less likely to be married than female schizophrenics.…”
contrasting
confidence: 42%
“…Most British studies demonstrate increased rates among West Indians (8,9,11,17,21) and West Africans (5, 19). Rates of diagnosed mental illness are affected by the type of diagnoses chosen; the perception of symptomatology, possibly confused with transcultural factors (paranoia and witchcraft beliefs), have been commonly noted among migrants (5,7,8,21,22); and the practice of combining diagnoses to obtain statistical significance, with inevitable loss of phenomenological definition.…”
mentioning
confidence: 99%
“…The earliest studies of the incidence of schizophrenia in the new migrant populations reported higher than expected rates in migrants of African-Caribbean origin. 4,5 There have subsequently been at least 18 studies investigating this issue, all of which have shown that rates are elevated in the AfricanCaribbean population relative to the white population (between 2 and 18 times). The validity of these findings has been the subject of intense debate in the UK, a debate partly fueled by the methodological shortcomings of early studies (eg, inadequate population denominator data, use of nonstandardized diagnoses, and uncertainty over the completeness of case ascertainment).…”
Section: Later Studies: the United Kingdommentioning
confidence: 99%
“…• Kiev (1965) reported a higher overall consultation rate among Black (Jamaican) primary care attendees in Brixton, south London. The rate of psychiatric disorder was also higher than among the White British population.…”
Section: Detection and Referral Of Psychiatric Morbiditymentioning
confidence: 99%